New Ratio Estimators for Estimating the Population Mean Using the Median and Size of the Sample - Dansawad, Napattchan (Burapha Science Journal, 2026)
This paper presents new ratio estimators for estimating the population mean using the median and size of the sample under simple random sampling without replacement (SRSWOR) scheme. The author has developed the estimator that proposed by Nangsue (2009), and Soponviwatkul and Lawson (2017). Furthermore, some important properties of the introduced estimators such as Bias, and Mean Squared Error (MSE) have been studied. In addition, theoretical and empirical studies were used in order to access the performance of the introduced estimators. The results of this study showed that the introduced estimators are more efficient than the usual unbiased estimator ( ), Cochran (1977) estimator ( ), Cochran (1977) estimator ( ), Sisodia and Dwivedi (1981) estimator ( ), Singh and Tailor (2003) estimator ( ),Subramani and Kumarpandiyan (2013) estimator ( ), Jerajuddin and Kishun (2016) estimator ( ), Nangsue (2009) estimator ( ), and the estimators of Soponviwatkul and Lawson (2017) ( , ) under percent relative efficiencies (PRE) criterion when the correlation between the study variable y and the auxiliary variable x is positive.